Analysis of well water feasibility as water consumption in Boarding House Area, Jember District Indonesia - Wanda Febrianty; Sudarti Sudarti (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2022)
Currently, as many as 45% of Indonesian people use well water to meet their daily needs. However, problems with the use of well water occur due to increasing population growth, resulting in increased water pollution. Waste generated by human activities can seep into the ground and contaminate well water. This research was conducted to determine the feasibility of well water as consumption water in the Kos area of ​​Jember Regency. The method used in this research is a descriptive observation method. The study used seven samples of well water originating from the Kos area of ​​Jember Regency and 1 sample of mineral water as a comparison. Samples of well mineral water were tested using physical, chemical, and biological tests. Physical tests were carried out on color, odor, temperature, and total dissolved solids (TDS). The chemical test was carried out in the form of a pH test. Biological tests were carried out by observing changes in color and odor due to bacteria after the samples were left for ten days. The results showed that three water samples did not meet the physics test, namely sample 4, sample 6, and sample 8. One well water sample did not meet the chemical test, namely sample 4. Five water samples did not meet the biological test: sample 2, sample 4, sample 6, sample 7, and sample 8.